2013
DOI: 10.1186/1472-6947-13-37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of data completeness in the electronic health record for the purpose of patient recruitment into clinical trials: a retrospective analysis of element presence

Abstract: BackgroundComputerized clinical trial recruitment support is one promising field for the application of routine care data for clinical research. The primary task here is to compare the eligibility criteria defined in trial protocols with patient data contained in the electronic health record (EHR). To avoid the implementation of different patient definitions in multi-site trials, all participating research sites should use similar patient data from the EHR. Knowledge of the EHR data elements which are commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 20 publications
(18 reference statements)
6
69
0
2
Order By: Relevance
“…6 In the Gopalan study, the researchers incorrectly assumed that, due to ADA guidelines, HbA1C would be tested at least once within a 6 month period. 7,8,9 One study has shown a high missing data rate but high accuracy for HbA1C data; 10 and a diabetes RCT has recognized and planned accordingly for missing HbA1C data. 11…”
Section: Study Design Recommendationsmentioning
confidence: 99%
“…6 In the Gopalan study, the researchers incorrectly assumed that, due to ADA guidelines, HbA1C would be tested at least once within a 6 month period. 7,8,9 One study has shown a high missing data rate but high accuracy for HbA1C data; 10 and a diabetes RCT has recognized and planned accordingly for missing HbA1C data. 11…”
Section: Study Design Recommendationsmentioning
confidence: 99%
“…Data extraction tools that access electronic medical record systems are increasingly being used for quality assurance activities within Australian primary care with recent attention being given to the validity of the information obtained [12,13]. One study has concluded that current tools may be unreliable [12] and recent experience has also raised concerns about the completeness of these data outside of formal research trials [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…32 This suggested that many EHRs may not be ready for clinical research, 33 or that the insurer's administrative data contained spurious diagnoses, 34 or both. We also had to exclude patients who met the inclusion criteria and had a known start date for outreach, but did not have any clinical measures such as HbA 1 c or LDL.…”
Section: Discussionmentioning
confidence: 99%